2017
DOI: 10.2196/jmir.7463
|View full text |Cite
|
Sign up to set email alerts
|

More Than a Text Message: Dismantling Digital Triggers to Curate Behavior Change in Patient-Centered Health Interventions

Abstract: Digital triggers such as text messages, emails, and push alerts are designed to focus an individual on a desired goal by prompting an internal or external reaction at the appropriate time. Triggers therefore have an essential role in engaging individuals with digital interventions delivered outside of traditional health care settings, where other events in daily lives and fluctuating motivation to engage in effortful behavior exist. There is an emerging body of literature examining the use of digital triggers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 89 publications
5
85
0
Order By: Relevance
“…show promising trends for the intervention to improve patient communication and promote self-care competence during pregnancy. These findings are consistent with recent research showing mobile phones to be an emerging health technology that can positively modify health behaviors (Abroms et al, 2015;Muench & Baumel, 2017;Singh et al, 2016). Additional research is needed that includes more at-risk participants who can benefit from the intervention and a larger sample to draw conclusions about intervention effectiveness and financial implications compared to usual prenatal care.…”
Section: Discussionsupporting
confidence: 88%
“…show promising trends for the intervention to improve patient communication and promote self-care competence during pregnancy. These findings are consistent with recent research showing mobile phones to be an emerging health technology that can positively modify health behaviors (Abroms et al, 2015;Muench & Baumel, 2017;Singh et al, 2016). Additional research is needed that includes more at-risk participants who can benefit from the intervention and a larger sample to draw conclusions about intervention effectiveness and financial implications compared to usual prenatal care.…”
Section: Discussionsupporting
confidence: 88%
“…These guiding prompts include a series of regular smart phone notifications to the user, once a day during the first 44 days. The delivery of prompts was designed to be consistent with the recommendations of previous research (Morrison et al, 2017;Muench & Baumel, 2017). Prompts were delivered with a controlled frequency and provided unique information each time.…”
Section: Using Guided Promptsmentioning
confidence: 99%
“…Prompts were delivered with a controlled frequency and provided unique information each time. Research has shown that uncontrolled frequency of prompts affects the effectiveness of the prompts, which may result in ignoring or stopping the use of the app (Fry & Neff, 2009;Morrison et al, 2017;Muench & Baumel, 2017).…”
Section: Using Guided Promptsmentioning
confidence: 99%
“…The overall goal of any digital communication‐based intervention for chronic disease management is to maximize persuasion to improve self‐care and minimize potential for patient fatigue or habituation. As shown in the framework presented by Muench and Baumel in 2017, several aspects of text message interventions can influence their effectiveness for improving adherence to antihypertensive pharmacotherapy. The first aspect is message source, which encompasses the patients’ perceptions of the source's credibility and affiliation.…”
Section: Text Message Intervention Features For Medication Adherencementioning
confidence: 99%